Thermо-induced Irreversible Changes of the Properties of Rats NADPH Oxidase - Simonyan, R. M.; Simonyan, G. M.; Babayan, M. A.; Simonyan, K. V.; Isoyan, A. S.; Darbinyan, L. V.; Simonyan, M. A. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
It is known that FAD is an important cofactor for Nox isoform, as an electron carrier from NADPH to Fe(III) of the heme group then to molecular oxygen reducing it up to О2 ~[1, 6]. On the other hand, the thermostable Nox is isolated from thermostable microorganisms [5]. However, the role of FAD as a factor in changing the conformation and thermostability of Nox isoform has not yet been determined. The aim of the present work was to determine the corresponding conditions under which the thermostability and production of superoxide radicals are also observed in the absence of NADPH. При сравнении оптических спектральных показателей нетермостабильных изоформ свежей НАДФH-оксидазы (fNox) из мембран эритроцитов и легких белых крыс (через 5-6 дней после ее получения) с аналогичными показателями несвежей Nox (nfNox), после хранения этих Nox в течение 20-25 дней в лиофилизированном состоянии наблюдалась более высокая термостабилизация изоформ nfNox и продукция супероксидных радикалов (О2 ~) в отсутствие НАДФH. Можно заключить, что в этих условиях в nfNox наблюдались необратимые конформационные изменения, обусловленные увеличением оптического поглощения ФАД (при 365 нм) в составе nfNox. Սպիտակ առնետների էրիթրոցիտների և թոքերի թաղանթներից (նրա ստացումից 5-6 օր հետո) թարմ NADPH օքսիդազի (fNox) ոչ ջերմակայուն իզոֆորմների օպտիկական սպեկտրային պարամետրերի համեմատությունը Nox-ի պահպանումից հետո ոչ թարմ Nox-ի (nfNox) նմանատիպ պարամետրերի հետ, 20-25 օրվա ընթացքում լիոֆիլացված վիճակում նկատվել են nfNox իզոֆորմների ավելի բարձր ջերմային կայունացում և սուպերօքսիդ ռադիկալների (О2 ~) արտադրություն NADPH-ի բացակայության դեպքում: Կարելի է եզրակացնել, որ այս պայմաններում nfNox-ում նկատվել են անդառնալի կոնֆորմացիոն փոփոխություններ՝ կապված nfNox-ի կազմի մեջ FAD-ի օպտիկական կլանման ավելացման հետ (365 նմ):
Keywords: Experimental and Preventive Medicine